Perilaku pencarian informasi pekerjaan oleh sarjana fresh graduate dengan analisis Model Wilson - Nihayati Nihayati; Laksmi Laksmi (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. This paper discusses information seeking behavior of university fresh graduate. In fact, many university graduates still face serious difficulties in the job search process based on the increasingly high unemployment rate. Data Collection Method. Purposive sampling was used with 10 respondents. Interviews were used as a data collection technique. Data Analysis. Miles and Huberman data analysis was used in this study reduction, data presentation and conclusion.. Resultsand Discussions. Two barriers in finding information were from psychological factors and interpersonal abilities. New graduates with low psychological and interpersonal skills, such as lack of self-confidence, confusion, inferiority, anxiety, lack of communication show uneffective search results. The situation where information sources are easily accessible supports faster information retrieval and vice versa. Our five informants who lived in the city with easy access support the infomatation seeking process. Conclusion Factors affecting information seeking behaviour were psychological situations, demographic circumstances, interpersonal abilities, environment and characteristics of information sources. Those five factors influence each other.